Work stress, workplace violence, job satisfaction and their effects on turnover intention among midwife and public health supervisor II in Myanmar - Tun, Nyein Aye; Mon, Khaing Lay; Hone, San; Lat, Tun Win; Win, Hla Hla (International Journal Of Community Medicine And Public Health, 2024)
Background: Increased work stress, decreased job satisfaction and increased turnover intention impair the quality of healthcare services. This study aimed to determine the current status of turnover intention, to assess the effects of work stress, workplace violence, and job satisfaction on turnover intention, and examine the mediation role of job satisfaction between associated factors and turnover intention. Methods: A cross-sectional analytical study was conducted in 2023. A total of 189 midwives (MW) and 205 public health supervisors (PHS II) participated. The relationships between work stress, workplace violence, job satisfaction on turnover intention were assessed using the Pearson correlation coefficient. Path analysis was performed to study the mediation role of job satisfaction. Results: Among the participants, (60.2%) had a high level of turnover intention, (7.4%) experienced high work stress and (23.9%) were dissatisfied with their jobs. Ninety-nine participants (25.13%) had been exposed to any type of workplace violence (physical, verbal, bullying or sexual harassment). Work stress was significantly positively correlated with turnover intention (r=0.4), while workplace violence had no significant correlation (r=0.006). Job satisfaction was significantly negatively correlated with turnover intention (r=-0.530). Job satisfaction had mediation role between work stress and turnover intention, but it had no mediation role between workplace violence and turnover intention. Conclusions: High turnover intention among participants is significantly associated with work stress and job satisfaction. An urgent and effective strategy is required to retain them.